Optical Coherence Tomography Angiography of Macular Features After Proton Beam Radiotherapy for Small Choroidal Melanoma - Sellam, Alexandre; Coscas, Florence; Lumbroso-Le Rouic, Livia; Dendale, Rémi; Lupidi, Marco; Coscas, Gabriel; Desjardins, Laurence; Cassoux, Nathalie (American journal of ophthalmology, 2017)
To describe the macular features of patients treated with proton beam therapy for choroidal melanoma (CM), using optical coherence tomography angiography (OCTA). Retrospective case-control study. This study included patients treated with proton beam radiotherapy (PBR) for a small CM. Only patients who had received 100% of the dose of 60 Gy external beam radiation to the macular area were included in the analysis. All the patients had undergone a full ophthalmologic examination, including visual acuity, optical coherence tomography B-scan, and OCTA. Qualitative and quantitative vascular features of the retinal plexus and the choriocapillaris were analyzed on OCTA and compared with those in healthy subjects matched on age and sex. Thirty-seven patients had undergone an OCTA after PBR for a small CM. Seventeen patients (9 men and 8 women) were included. The mean age of the patients was 56.6 years (range, 28-86). At presentation, the mean tumor thickness was 3.39 mm (range, 1.3-7.0 mm). The mean follow-up duration was 35.8 months (range, 11-72 months). Thirteen patients (76.5%) had a clinical radiation maculopathy; 8 patients (47.1%) had macular cysts on OCT-B scan. All patients (100%) had abnormalities on OCTA. Some “signal void” spots were detected at the level of the choriocapillaris in 15 patients (88.2%). The mean vascular density (regarding the full retina) was significantly lower in the patients treated with PBR than in healthy subjects (P < .0001). Patients treated with PBR for CM (with 100% of the dose given to the macula) present major changes at both plexuses but also a vascular rarefaction of the choriocapillaris.